(untitled) (Olhar de Professor, 2023)
History bequeathed to us the birth of the bifurcation between left and right as a contingent product of the spontaneity of a material change, a radical re-structuring of the physical scenario in which political decisions had to be taken, which gave birth to a dual politics, then, what is the structural change that will make possible the birth of a new way of doing politics in our times? This paper introduces a new critical perspective to the debates around the dichotomy of left and right in the field of politics. It is argued that we actively participate in the ghostly condition that politics maintains, a politics emptied of meaning and significance, which survives by offering generalized and desperate solutions. The problem of the scarce delimitation of these concepts and the evident mixture in the political projects of our time, requires a documentary systematization-reading and a philosophical analysis of the extensive theoretical proposals that try to approach the phenomenon. Through the analysis of the historical, political, social and economic uses that have been inserted in the left and right concepts since early times, we have been introduced in the quagmire of the crisis of legitimacy that exists in politics in order to rethink the future.